Social mobility as a factor of maintaining of the ethnic identity: the comparative analysis of koreans in Japan and CIS countries - Ем, Н; Мионг, Сун Ок; Чан, Бенг Сун (Journal of Oriental Studies, 2018)
Korean international diaspora is presented in many countries of the world. The study of Korean diaspora in Japan remains one of the less researched issue in Post soviet realm. The object of the research is Koran diaspora in Japan as in monoethnic country and in countries of the former Soviet Union as on poly-ethnic society. Japan originally is monoethnic country. The notion of the monoethnicity is very stable and the comprehension of this is rooted in the perception of the social scientists on the level of the myth. Insimilar vein, more than 600000 Koreans reside in Japan as «invisible minority». The history of appearance of the Korean diaspora in Japanese archipelago began from Korea becoming a colony of Japan. The ethnic variety in former Soviet Union amount for more than one hundred nationalities and history of settling is connected to deportation.Koreans of Japan dominate among minorities of the accepting society.According the population census in 2000 there were 528904 Koreans in Japan. Korean diaspora amount the biggest group after Chinese, Brazilian and Pilipino. Koreans of CIS (the total number is 500000) includes Korean Diasporas, with the major number in Uzbekistan 198000, Russia 125000, and Kazakhstan 105000. The subject of the consideration is the level of maintaining of the ethnic identity of Koreans in Japan and in countries of CIS. It is supposed that maintaining of the ethnic identity influence the factors of the social mobility as in example of the level of the education,socio-economic status and level of naturalization of Koreans in Japan( as in intermarriage example). The purpose of the research is the showing the factors that influence the maintaining of the ethnic identity in foreign environment taking Korean diaspora in Japan as example. The purpose of the research is study and comparison of the problems and peculiarities of the adaptation and integration of the ethnic Koreans in accepting society to take Japan and CIS as an example. In Korean society there is «new hybrid identity»when the relation to ethnos is characterized as identity as blood linage and identity of residence. Not the last role-plays the level of the education and social status of Koreans. The higher the constituents the higher and equal the love to «mother and father» as to «identity of Korean ethnos and ethnos of accepting society.»